2018
DOI: 10.1136/tobaccocontrol-2018-054404
|View full text |Cite
|
Sign up to set email alerts
|

Testing messages about comparative risk of electronic cigarettes and combusted cigarettes

Abstract: Comparative risk communication might encourage smokers to switch to lower-harm tobacco products. Comparative risk messages with more negative antismoking elements in the design might be particularly effective, because they led to higher self-efficacy to quit smoking. Regulatory agencies may consider using comparative risk messages with more negative antismoking elements to educate the public about lower risk of e-cigarettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 67 publications
0
39
0
Order By: Relevance
“…Recently, researchers have begun evaluating messages about comparative risks of electronic and combusted cigarettes 17–24. Quantitative studies of comparative risk messages have reported mixed findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have begun evaluating messages about comparative risks of electronic and combusted cigarettes 17–24. Quantitative studies of comparative risk messages have reported mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies of comparative risk messages have reported mixed findings. While some studies found that comparative risk messages may encourage smoking cessation,20 24 reduce perceived risk of e-cigarettes relative to cigarettes, and may not change dual use intentions,21 24 others found that comparative risk messages may increase dual use intentions among smokers 21 22. Given the mixed findings and the challenges of developing comparative risk communication about e-cigarettes, there is a need for an in-depth understanding of the impacts and important aspects of comparative risk messages.…”
Section: Introductionmentioning
confidence: 99%
“…Key measures are shown in Table 1. Outcome variables included perceived addictiveness of nicotine and perceived risk of nicotine [5], perceived e-cigarette risk (absolute [14,15] and comparative [15,16]), and behavioral intentions (intentions to switch to e-cigarettes [15], e-cigarette and cigarette dual use intentions [15], and intentions to seek information about e-cigarettes [17][18][19][20]). Covariates included gender, age, race, education, daily vs. non-daily smoking, use of e-cigarettes (current vs. former vs. never use), quit attempt in the past 12 months, smoking identity [21], and pre-exposure perceived comparative risk of e-cigarettes, perceived addictiveness of nicotine, and perceived risk of nicotine.…”
Section: Key Measuresmentioning
confidence: 99%
“…Because the perception that ENDS are less harmful than cigarettes is usually cited as one of the most important reason for their use [ 8 , 9 ], it is imperative to understand how to communicate to the public about the comparative risk of ENDS and cigarettes. However, only a few studies have examined the effects of messages communicating the risk differential between ENDS and combusted cigarettes [ 10 , 11 , 12 , 13 , 14 , 15 ]. These studies found that comparative risk messages about ENDS were able to reduce smokers’ perceived risk of ENDS relative to combusted cigarettes [ 13 , 14 , 15 ], increase smokers’ interest in using ENDS [ 10 , 16 ], and reduce smoking intentions [ 15 ] and smoking behavior during the study [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies have examined the effects of messages communicating the risk differential between ENDS and combusted cigarettes [ 10 , 11 , 12 , 13 , 14 , 15 ]. These studies found that comparative risk messages about ENDS were able to reduce smokers’ perceived risk of ENDS relative to combusted cigarettes [ 13 , 14 , 15 ], increase smokers’ interest in using ENDS [ 10 , 16 ], and reduce smoking intentions [ 15 ] and smoking behavior during the study [ 17 ]. Despite these promising findings, two studies concluded that messages presenting lower risk information about ENDS relative to cigarettes had no effects on smoking cessation intentions [ 15 , 17 ].…”
Section: Introductionmentioning
confidence: 99%